Reseñas - Maria Amalia Barchiesi; Marina Bianchi; Daniele Crivellari; Emanuele Leonardi; Giovanna Minardi (Cuadernos AISPI, 2016)
Emanuela Jossa, Raccontare gli animali. Percorsi nella letteratura ispanoamericana, Firenze, Le Lettere, 2012, 355 pp. ISBN 9788860876157